Sosialisasi sehat tanpa hipertensi (SEHATI) pada ibu kader PKK sebagai upaya pencegahan hipertensi - Azizah Puspaningtyas; Ayik Mirayanti Mandagi (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Hypertension is a public health issue with a high prevalence, particularly among women of reproductive age. Limited early detection and knowledge regarding hypertension prevention at the community level necessitate educational interventions. The